The role of institutional factors when determining investment strategies of sovereign wealth funds in stock market - AKYOL, Mehmet; ÇİÇEN, Yıldırım Beyazıt (Turkish Economic Review, 2017)
Abstract. Sovereign Wealth Funds (SWF) are investment vehicles of governments which use its assets in hand for the favor of public interest. SWFs invest a vast amount of money that varies in amount from year to year both in national and international platforms. Funds which provide an excellent source mean a lot for developed countries as much as they mean to developing countries. In this study, the factors SWFs consider while investing in the stock market are analyzed. Panel data is chosen for analysis using SWF and Heritage institutional factor index. New Zeeland is selected as example to illustrate that from which institutional factor, such as private property right, law enforcement, tax responsibility and freedom of labor, influenced investments New Zeeland SWF made in stock markets of 42 different countries. Keywords. Sovereign Wealth Funds, Stock markets, Investment, Institutional factors. JEL. C10, C23, G23.